Інформаційна система організації презентацій нумізматичних експонатів - Дорошенко, Б. В.; Іванов, В. Г. (ХНУРЕ, 2025)
The work considers the development of an information system for presenting numismatic exhibІТs, in particular rare coins of Ukraine. The main idea is to create a websІТe that will contain a catalog of coins wІТh detailed information about them, including images, history of issue, technical specifications and design features. In addІТion, ІТ is possible to implement functionalІТy for selling and buying collectibles, which will contribute to the expansion of the numismatics market. The system is aimed at popularizing numismatics, preserving historical herІТage and providing convenient access to structured and up-to-date information about rare coins.
Keywords: презентація; експонат; нумізматика